Floods connect tropical river–floodplain food webs but shrink fish community isotopic trophic niches - Colton N. Perna; Luke McPhan; Timothey D. Jardine; Lauren Meyer; R. Keller Kopf (Hydrobiologia, 2026)
Lateral connectivity between the floodplain and river channel is hypothesised to expand fish community isotopic trophic niches and increase overlap of river–floodplain food webs. To evaluate how flood magnitude influences trophic dynamics in a large tropical free-flowing river (Roper River, Australia), we measured community isotopic niches in low- and high-magnitude flood years in wetland and river habitats. Contrary to our hypothesis, isotopic niche area of the river fish community contracted following the high-magnitude flood year, when compared to a low-magnitude flood year. Wetland fishes maintained more similar niche space regardless of flood conditions, but showed the same pattern of contracting niche area following a large magnitude flood. Niche overlap was lowest for river low-magnitude flood and wetland high-magnitude flood and highest for river and wetland high-magnitude flood. Our results suggest that river–floodplain fish communities exploit a wider isotopic range of food sources during low-flood years, including enriched sources of potentially marine origin, while sharing abundant less diverse resources in high-magnitude flood years. As water resources in tropical rivers are developed, our findings highlight the importance of conserving multiple dimensions of connectivity in riverine landscapes to maintain intact river–floodplain food webs.